COMPARISON OF RELIGIOUS RHETORIC K.H. ABDULLAH GYMNASTIAR WITH HABIB MUHAMMAD RIZIEQ: PERBANDINGAN RETORIKA DAKWAH K.H. ABDULLAH GYMNASTIAR DENGAN HABIB MUHAMMAD RIZIEQ - Sabrina Fadilah Az-zahra; Nadra Nadra; Sawirman Sawirman (LLDIKTI Wilayah X, 2021)
This research aims to (1) describe the differences in the religious rhetoric of Aa Gym's from Habib Rizieq’s in terms of ethos, pathos, and logos; (2) describe the different rhetorical canons used; and (3) determine the elements of rhetorical content contained in both orator. This research uses a qualitative descriptive approach. The data were taken from the religious speech of Aa Gym and Habib Rizieq with the same theme available on the YouTube platform, which is about leaders and leadership. The research shows the following results. (1) The religious rhetoric of Aa Gym and Habib Rizieq both use all persuasion tools in the form of ethos, pathos, and logos. However, there are three aspects that are controlled by Aa Gym in terms of ethos, namely good competence, good moral character, and goodwill, while only two aspects are controlled by Habib Rizieq, namely good competence and goodwill. (2) All of the rhetorical canons were used by the two preachers, but there are still doubts about their application to Aa Gym. (3) Aa Gym's rhetoric belongs to the type of epideictic rhetoric with a few elements of deliberative rhetoric. Meanwhile, Habib Rizieq's rhetoric belongs to the type of epideictic and deliberative rhetoric with a few elements of forensic rhetoric.